Unrelated donor versus matched sibling donor in adults with acute myeloid leukemia in first relapse: an ALWP-EBMT study. Issue 1 (December 2016) - Ruggeri, Annalisa; Battipaglia, Giorgia; Labopin, Myriam; Ehninger, Gerhard; Beelen, Dietrich; Tischer, Johanna; Ganser, Arnold; Schwerdtfeger, Rainer; Glass, Bertram; Finke, Jurgen; Michallet, Mauricette; Stelljes, Matthias; et al.
Abstract Background Allogeneic stem cell transplantation is the only curative option for patients with acute myeloid leukemia (AML) experiencing relapse. Either matched sibling donor (MSD) or unrelated donor (UD) is indicated. Methods We analyzed 1554 adults with AML transplanted from MSD (n  = 961) or UD (n  = 593, HLA-matched 10/10, n  = 481; 9/10, n  = 112). Compared to MSD, UD recipients were older (49 vs 52 years, p  = 0.001), transplanted more recently (2009 vs 2006, p  = 0.001), and with a longer interval to transplant (10 vs 9 months, p  = 0.001). Conditioning regimen was more frequently myeloablative for patients transplanted with a MSD (61 vs 46 %, p  = 0.001). Median follow-up was 28 (range 3–157) months. Results Cumulative incidence (CI) of neutrophil engraftment (p  = 0.07), grades II–IV acute GVHD (p  = 0.11), chronic GVHD (p  = 0.9), and non-relapse mortality (NRM, p  = 0.24) was not different according to the type of donor. At 2 years, CI of relapse (relapse incidence (RI)) was 57 vs 49 % (p  = 0.001). Leukemia-free survival (LFS) at 2 years was 21 vs 26 % (p  = 0.001), and overall survival (OS) was 26 vs 33 % (p  = 0.004) for MSD vs UD, respectively. Chronic GVHD as time-dependent variable was associated with lower RI (HR 0.78, p  = 0.05), higher NRM (HR 1.71, p  = 0.001), and higher OS (HR 0.69, p  = 0.001). According to HLA match, RI was 57 vs 50 vs 45 %, (p  = 0.001) NRM was 23 vs 23 vs 29 % (p  = 0.26), and LFS at 2 years was 21 vs 27 vs 25 % (p  = 0.003) for MSD, 10/10, and 9/10 UD, respectively. In multivariate analysis adjusted for differences between the two groups, UD was associated with lower RI (HR 0.76, p  = 0.001) and higher LFS (HR 0.83, p  = 0.001) compared to MSD. Interval between diagnosis and transplant was the other factor associated with better outcomes (RI (HR 0.62, p  < 0.001) and LFS (HR 0.67, p  < 0.001)). Conclusions Transplantation using UD was associated with better LFS and lower RI compared to MSD for high-risk patients with AML transplanted in first relapse.